STUDENT PERCEPTION OF REWARD PROVISION ON STUDENTS LEARNING MOTIVATION OF CLASS V SD MUHAMMADIYAH 6 PEKANBARU - Rila Afrila; Syahrilfuddin Syahrilfuddin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to determine students’ perceptions about giving rewards to the learning motivation of five grade student at SD Muhammadiyah 6 Pekanbaru. This research is quantitative research, which was held at SD Muhammadiyah 6 Pekanbaru. The sample in this study amounted to 47 respondent namely all fifth-grade student SD Muhammadiyah 6 Pekanbaru. Data analysis techniques using quantitative analysis technique by testing and processing data obtained from questionnaires that have been filled out by respondent. The validity of the questionnaire by testing it at SD Negeri 37 Pekanbaru, then the data is processed using SPSS version 22.0 to find a valid statement. Reliability tests were carried out using the SPSS version 22.0 program with alpha Cronbach's values above 0,60. In the t-test of two variables, where t arithmetic is greater than t table that is equal to 6,175 > 1,679. In the normality test, the data obtained is greater than 0,05 which is 0,386 which means the data contribute normally. The resulting regression equation Y = 14,051 + 0,491x with a coefficient of determination of 37% and the rest is correlation by other factors not examined by researchers. This can be interpreted that the more positive the perception of students in giving rewards the higher the motivation to learn.